Analysis of endoscopic features for histologic discrepancies between biopsy and endoscopic submucosal dissection in gastric neoplasms: 10-year results. Issue 1 (January 2019) - Noh, Choong-Kyun; Jung, Min Wook; Shin, Sung Jae; Ahn, Ju Young; Cho, Hyo Jung; Yang, Min Jae; Kim, Soon Sun; Lim, Sun Gyo; Lee, Dakeun; Kim, Young Bae; Cheong, Jae Youn; Lee, Kee Myung; et al.
Abstract: Background and aim: The histologic discrepancies between preoperative endoscopic forceps biopsy (EFB) and endoscopic submucosal dissection (ESD) specimens sometimes confuse the endoscope operator. This study aimed to analyze the limitation of the biopsy-based diagnosis before ESD and to evaluate which factors affect the discordant pathologic results between EFB and ESD. Methods: A total of 1427 patients, who were diagnosed with gastric adenoma by EFB, were enrolled. Cancer confirmed on EFB was excluded (n = 513). We retrospectively reviewed cases and compared histologic diagnoses in the biopsy sample with the final diagnosis in the endoscopically resected specimen. Results: The diagnosis was upgraded (from low-grade dysplasia to high-grade dysplasia or adenocarcinoma, or from high-grade dysplasia to adenocarcinoma) in 328 cases (23.0%), concordant in 944 (66.1%), and downgraded (from high-grade dysplasia to low-grade dysplasia or non-neoplasia, or from low-grade dysplasia to non-neoplasia) in 155 (10.9%). Multivariate logistic regression analysis showed that surface ulceration and depressed lesions were associated with significant risk factors for upgrading. Age younger than 60 years and size <1 cm were associated with significant factors for downgrading. Conclusions: Careful endoscopic observation should consider size, ulceration, and depression to ensure accurate diagnosis when a gastric neoplasm is suspected.